Clinical and genetic analysis of a Chinese family with GM1 gangliosidosis caused by a novel mutation in GLB1 gene - Zhang, Biao; Huang, Xiao-li; Lu, Xin-xin; Huang, Heng-bin; Wu, Yan-an (Frontiers in Pediatrics, 2025)
ObjectiveTo describe the clinical presentation and novel mutation in the ganglioside-beta-galactosidase gene (GLB1) gene in a Chinese family with GM1 gangliosidosis.MethodsWe collected clinical data from a Chinese family with GM1 gangliosidosis, and performed whole exon sequencing (WES) of the proband and his parents. The pathogenic sites of candidate genes were targeted, and the detected exon mutations were verified by Sanger sequencing. Enzyme activity of β-galactosidase was detected in 293T cells transiently transfected with plasmids encoding the detected mutations.ResultsTwo siblings in this family presented with neurological degeneration, and were classified as the late-infantile type. Two siblings and their parents underwent WES of the peripheral blood. A reported missense mutation c.446C>T and a novel mutation c.1058_1059delinsAA in GLB1 gene inherited from the mother and father respectively were identified. The mutant c.1058_1059delinsAA retained β-galactosidase activity at 0% of wild-type GLB1.ConclusionThis study identified a novel mutation of the GLB1 gene in a Chinese family with GM1 gangliosidosis and provided new insights into the molecular characteristics and genetic counseling of GM1 gangliosidosis.